The Effect of Work Environment and Work Ability on Employee Performance at CV Bias Azizah - Dede Supian; Syahrul Muharam Putra Nugraha (International Journal of Economics (IJEC), 2022)
Performance is very important in companies and management, there are many factors that affect employee performance. This study entitled "the influence of the work environment and work ability on performance". The purpose of this study was to determine the effect of the work environment and work ability on employee performance The research method uses descriptive and associative methods with a quantitative method approach, the research population is CV employees. Azizah's bias, totaling 35 people, was sampled using the non-probability sampling technique of saturated samples. Data analysis techniques used validity test, reliability test, Pearson product moment correlation test and coefficient of determination test. The data obtained was processed using the SPSS software program version 23. The results of partial simple correlation testing work environment and work ability affect employee performance with correlation coefficient values ​​of 0.377 and 0.594 respectively. Simultaneous multiple correlation testing of work environment and work ability variables has a positive effect on employee performance. This can be seen from the multiple correlation coefficient of 0.595 ''medium'' in the interval 0.40-0.599. This confirms that the work environment and work ability simultaneously can be used as an effort to improve employee performance.